Teacher Professionalism in Taare Zameen Par: A Qualitative Analysis - Fity Amanda; Mahariah Mahariah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
Teacher professionalism is essential to creating humanistic, inclusive, and student-centered learning that recognizes students’ diverse characteristics and potential. This study aims to analyze the representation of teacher professionalism in the film Taare Zameen Par and its relevance to the principles of Islamic education. The study employed a qualitative descriptive approach, using the film as the primary data source and relevant books and journal articles as secondary sources. Data were collected through indirect observation and documentation by repeatedly observing dialogues, scenes, behaviors, and actions related to teacher professionalism, and were analyzed through data reduction, data presentation, classification, interpretation, and conclusion drawing. The findings indicate that teacher professionalism in Taare Zameen Par is represented through four interconnected competencies: pedagogical, personal, social, and professional competencies. These competencies are reflected in Ram Shankar Nikumbh’s ability to understand students’ individual needs, develop creative and appropriate learning strategies, communicate effectively with students, teachers, parents, and the community, and demonstrate patience, empathy, responsibility, emotional maturity, and exemplary behavior. From the perspective of Islamic education, these characteristics are consistent with the values of uswah (exemplary conduct), ihsan (excellence), compassion, responsibility, and respect for human potential. The study concludes that teacher professionalism extends beyond mastery of subject matter and teaching skills, encompassing ethical character, social relationships, empathy, and commitment to developing each student’s potential. Future research may compare teacher professionalism across educational films or examine it more specifically through Islamic educational values.